The cervical spine of Australopithecus sediba. Issue 104 (March 2017) - Meyer, Marc R.; Williams, Scott A.; Schmid, Peter; Churchill, Steven E.; Berger, Lee R.
Abstract: Cervical vertebrae are rare in the early hominin fossil record, presenting a challenge for understanding the evolution of the neck and head carriage in hominin evolution. Here, we examine the cervical vertebrae of Australopithecus sediba, which unlike other South African taxa is known from associated cervical vertebrae. The A. sediba cervical vertebrae exhibit human-like values for wedging, pedicle cross-sectional areas, and articular facet heights, indicating reduced ventral loading relative to African apes. These features combine with a pattern of vertebral body bone distribution and caudally progressive size expansion suggesting a mode of cervical lordosis, load mitigation, and head carriage similar to humans and distinct from the cantilevered mode of head carriage of the extant African great apes. Yet these derived features in A. sediba are accompanied by ape-like vertebral body and dorsal pillar sizes, articular facet orientation, and uncinate process morphology signaling reduced lateral and rotational coupled movements between vertebral elements and indicate a considerably stiffer neck than in humans. A primitively long and horizontally-oriented C7 spinous process is likely related to a prognathic viscerocranium, although the complimentary C3 spinous process is short, implying large moments emanating from scapular and shoulder elevators rather than large muscles of head stabilization. Cross-sectional spinous process shape and robust anterior tubercles similarly signal increased arm elevation consistent with climbing behavior in corroboration with arboreal signatures previously observed in the shoulder, arms, and hand of A. sediba . Spinal canal shape and size suggests that A. sediba lacked the cervical spinal cord enlargement of Homo that confers humans with enhanced motor control to the upper limbs. The cervical spine of A. sediba thus presents a mosaic of primitive and derived characters, with anatomical features relating to neck posture and head carriage mirroring humans juxtaposed with most other aspects of functional anatomy that resemble chimpanzees.